Por uma outra geografia escolar: o prescrito e o realizado na atividade de ensino-aprendizagem de geografia - Spegiorin, Mônica de Toledo e Silva (2007)
In broad terms, this research aims at examining the relationship between the theoretical-methodological assumptions found in prescribed documents that guide the work of Geography teachers founding concepts of Critical Geography, the National Curricular Parameters (PCN) and the Pedagogic Project (PP) and the actual teaching-learning activity that is fulfilled in the school where the research is conducted. Framed within the Critical Applied Linguistics area (Pennycook, 2004), following the socio-historical-cultural (Vygotsky, 1934/1993) theoretical perspective and the principles of critical research of collaboration PCCol (Magalhães, 2004), this research aims at analysing the theoretical-practical relationship within the fulfillment of the Geography teaching-learning activity. It is, therefore, an investigation that discusses the institutional context - as well as the school culture - in which the participants are involved, as influential factors for the theoretical, didactic and pedagogical choices, from the point of view of the theoretical perspective propose by the Socio-Historical-Cultural Activity Theory (Leontiev, 1977), the Linguistic Theory of Enunciation (Bakhtin, 1929/1988), the idea of Critical Reflection (Freire, 1970; Smyth, 1992; Schön, 1992, 2000; Kemmis, 1987) and the concept of Critical Geography (Milton Santos, 1980, 1997). More specifically speaking, by means of the research that was carried out, this thesis aims at demonstrating the relationship between senses and meanings attributed by teachers to the work that they carry out, and which - often from an alienated or unconscious standpoint maintains the school-taught Geography on a position of being a descriptive and memorizing area of study. This inevitable maintains the school-taught Geography at a distance from a critical-citizenship education and from the learning of how to read the geographic space as a means to understanding reality. In terms of data analysis, the work is base don Bronckart (1997) and on the interpretation categories proposed by the Socio-Historical-Cultural Activity Theory (Engeström, 1998), with a view to identifying rules, labor division, instruments, the role that the community plays, the subject and the object that might allow us to understand the organization of the Geography teaching-learning activity. Results show that the knowledge of content found in prescribed materials does not guarantee use in the daily school life due to the impositions that the system and the school culture bring to the classroom